The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1152/japplphysiol.00960.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ozone on airway and tissue mechanics in obese mice

Abstract: Obesity is an important risk factor for asthma. We recently reported increased ozone (O(3))-induced hyperresponsiveness to methacholine in obese mice (Shore SA, Rivera-Sanchez YM, Schwartzman IN, and Johnston RA. J Appl Physiol 95: 938-945, 2003). The purpose of this study was to determine whether this increased hyperresponsiveness is the result of changes in the airways, the lung tissue, or both. To that end, we examined the effect of O(3) (2 parts/million for 3 h) on methacholine-induced changes in lung mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
67
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 49 publications
(76 reference statements)
11
67
1
2
Order By: Relevance
“…Ozone has been shown to exacerbate asthma and increase airway hyperreactivity (5,6), and to contribute to increased morbidity and mortality in patients with chronic obstructive pulmonary disease (COPD) (7,8). Similar alterations in lung function and increases in sensitivity to ozone have been described in animal models of asthma and allergic inflammation (9)(10)(11).…”
mentioning
confidence: 84%
“…Ozone has been shown to exacerbate asthma and increase airway hyperreactivity (5,6), and to contribute to increased morbidity and mortality in patients with chronic obstructive pulmonary disease (COPD) (7,8). Similar alterations in lung function and increases in sensitivity to ozone have been described in animal models of asthma and allergic inflammation (9)(10)(11).…”
mentioning
confidence: 84%
“…Increased responses to ozone are also reported in different models of obese mice (19,74,75). Williams and colleagues showed that augmented airway inflammation and reactivity in obese mice in response to ozone depended on TNFa (22).…”
Section: Irritant-and Pollutioninduced Asthma In Obesitymentioning
confidence: 95%
“…Largely through the work of Shore et al, molecular and physiologic characteristics of the murine model of obese asthma are currently being elucidated. 23,[26][27][28][29][30][31][32][33][34] However, assessing lung inflammation and lung responses among obese children remains challenging and limited by current technologies. Studies in children involving bronchodilator responsiveness, bronchoconstricting agonists (e.g., methacholine challenge), and airway inflammatory markers have yet to show the same consistent pattern of hyperresponsiveness that have been demonstrated in mice.…”
Section: If Obesity Leads To Asthma What Is the Mechanism?mentioning
confidence: 99%